The role of family harmony, emotion-focused coping, stressful life events on non-suicidal self-injury behavior in adolescents - Yudiyasiwi, Feslika Rezki; Anganthi, Nisa Rachmah Nur (Jurnal Ilmiah Psikologi Terapan, 2024)
Non-suicidal self-injury (NSSI) is the most significant health problem in the world for adolescents. The purpose of the study is to test the role of family harmony, emotion-focused coping, and stressful life events in non-suicidal behaviour in adolescents. This research uses a quantitatively correlational design. Sample study: 304 students at State Vocational High Schools in West Java, consisting of boys and girls aged 13–19 years. For the technique of taking samples, this study uses cluster random sampling. The family harmony scale, the emotion-focused coping scale, the stressful life events, and the non-suicidal self-injury scale are the measuring tools used in this study. The data analysis technique used was multiple regression analysis. There was a significant role among harmony family, emotion-focused coping, and stressful life events in influencing non-suicidal self-injury behavior in adolescents (r = .47, R2 = .22, p  <  .05.). The contribution of harmonious families was effective at 14.38%, followed by stressful life events at 5.45% and emotion-focused coping at 2.51%. This study proves that the most potent predictor of non-suicidal self-injury behavior in adolescents is family harmony. The study is expected to increase the outlook on the importance of guarding harmony, family, and stability through education or training facilitated by school.